Analysis and Calculation of Energy Storage Configuration in Power System - Yu DONG; Gaofeng FAN; Cun DONG; Ruoying YU; Junyi ZHAO (Zhongguo dianli)
At present, the configuration analysis and calculation of energy storage are mostly carried out around a single scene, which cannot give full play to the multiple functions of energy storage. Therefore, this research was conducted to achieve an orderly energy storage configuration and promote the comprehensive benefits of the power system. Starting from the overall operation demand of the power system, this paper summarized three key factors that should be considered for the energy storage configuration: the source-grid-load development, the replacement effect of energy storage on conventional units, and the comprehensive optimization of energy storage charging/discharging strategies. Then, an innovative analysis and calculation method for the overall configuration of energy storage in the power system was proposed in the case of uncertain power, energy, and charging/discharging time. The method included the initial value calculation of energy storage power, energy analysis and calculation under determined power, and energy rolling calculation under different power. Finally, a provincial power system was taken as a case to analyze and calculate the energy storage configuration from 2021 to 2025. The calculation results showed that the energy demand of the system could be reduced to a certain extent if the configuration had multiple feasible solutions and the energy storage power increased within a certain range. For economic consideration, the one with the least investment cost was chosen from all the feasible solutions as the final configuration scheme.